Suci: funeral management set / Mohamed Adli Mohamed Yusof ...[et al.] - Mohamed Yusof, Mohamed Adli; Ismail, Haziq Syakir; Mohd Faizar, Muqri Azfar; Asrul Effendi, Aiman Danial; Azman, Muhammad Nasir (2023)
The business name is Suci funeral management set. The set contains every possible thing needed to manage a funeral. We divided the sets into two category, men and women. Everything inside the sets is similar the only different is the measurement of the shround. In the male set the measurement of the shround is 10 meters and in the women’s, set is 2 meters longer equal to 12 meters all together. In each box contains shround (men/female), sintok root, camphor, cotton roll, gloves, sandalwood powder, soap, cotton bud, face mask, scissors, and attar oil. The meaning of Suci in English is holly and that is the reason why the partners agree on the name as managing a funeral is a holly act. This business does not have a shop to promote our funeral set as our target market is mainly focus on mosque. Our business office is located at Avenue Cress Seksyen 22, Shah Alam. Our main customer target is at Selangor and Wilayah Persekutuan. Our selling price for each set men and female is RM 168. The expected first year income for this business is RM 328,608. As this is a new business, there a little to non-achievement that’s been achieve by this business, but everything is possible so as this business. This business can offer a lot of achievement in the future. There are 5 workers in total which each people have its own work and responsibility. The first worker is the General Manager followed by the marketing manager followed by the administration manager followed by the operation manager and lastly the financial manager.